Rex finds an egg - Cushman, Doug (Cushman, Doug. Rex & Oslo., 2024)
Rex the warthog and Oslo the oxpecker bird are friends who do everything together. One day, they find an egg. Could it belong to a fish, a turtle, or even a dinosaur? Rex and Oslo find out together!